2013
DOI: 10.1016/j.chemosphere.2012.06.065
|View full text |Cite
|
Sign up to set email alerts
|

Chemical speciation and mobilization of copper and zinc in naturally contaminated mine soils with citric and tartaric acids

Abstract: A one-step extraction procedure and a leaching column experiment were performed to assess the effects of citric and tartaric acids on Cu and Zn mobilization in naturally contaminated mine soils to facilitate assisted phytoextraction. A speciation modeling of the soil solution and the metal fractionation of soils were performed to elucidate the chemical processes that affected metal desorption by organic acids. Different extracting solutions were prepared, all of which contained 0.01 M KNO(3) and different conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(33 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…Previous studies found that the fraction of metal existing in exchangeable form have the highest mobility. Carbonate bound and Fe-Mn oxide bound metal fractions were sensitive to pH changes and more likely to mobilize and release from the sediment under low pH (Pérez--Esteban et al 2013, Equeenuddin et al 2013. Under the middle to alkaline pH in this research, most of the metals were partitioned into carbonate and Fe-Mn oxyhydroxides, thus the released metals in the overlying water should mostly come from exchangeable fraction.…”
Section: Characterization Of Sedimentmentioning
confidence: 62%
See 1 more Smart Citation
“…Previous studies found that the fraction of metal existing in exchangeable form have the highest mobility. Carbonate bound and Fe-Mn oxide bound metal fractions were sensitive to pH changes and more likely to mobilize and release from the sediment under low pH (Pérez--Esteban et al 2013, Equeenuddin et al 2013. Under the middle to alkaline pH in this research, most of the metals were partitioned into carbonate and Fe-Mn oxyhydroxides, thus the released metals in the overlying water should mostly come from exchangeable fraction.…”
Section: Characterization Of Sedimentmentioning
confidence: 62%
“…Many researchers reported that at low pH the metal release was more obvious than at middle or high pH, however, the low pH instances are very rare in natural environment (Butler 2009, Watmough et al 2007, Pérez-Esteban et al 2013, Yang et al 2006, Jing et al 2007). So in this study, only middle and high pH effects were investigated.…”
Section: Characterization Of Sedimentmentioning
confidence: 99%
“…The authors concluded that the combination of two or more amendments was effective for improving phytoremediation of metal contaminated sites by Lolium perenne (Gunawardana et al, 2011). However, care should be taken when applying amendments to improve trace metal bioavailability because leaching to groundwater and thus groundwater pollution can occur (Perez-Esteban et al, 2013).…”
Section: A Bioavailabilitymentioning
confidence: 99%
“…In general, organic acids can bind trace metal ions in soil solution by complexation reactions, making them more available for plant uptake (Wang and Zhong, 2011). However, organic acids can also reduce the soil pH and solubilize some non-labile fraction of trace metals in soil, thus enhancing trace metal availability (Perez-Esteban et al, 2013).…”
Section: Root Chelation and Compartmentationmentioning
confidence: 99%
See 1 more Smart Citation